Technological Solutions to Decrease Protein Content in Piglet Weaning Feed, Improving Performance, Gut Efficiency, and Environmental Sustainability - Michele Lanzoni; Paul De Smet; Giovanni Ferrari; Davide Bochicchio; Sujen Santini; Valerio Faeti (Animals, 2025)
The trial explored innovative low-protein diets for weaning piglets, testing the elimination of fish meal and blood derivatives. The trial compared three treatments, each with two post-weaning feeds: control feed with blood plasma and fishmeal; T1: low-protein feed with seven amino acids, fishmeal, and blood plasma; T2: low-protein feed with seven amino acids without fishmeal and blood plasma. The trial tested 180 weaned piglets, 24 days of age, evenly distributed by weight, age, and litter of origin. At the end of the first phase, T1 and T2 recorded a significantly higher average weight, ADG, and FCR compared with the control feed. At the end of the second phase, the T2 group maintained a significantly better weight, ADG, and FCR than the control group. Considering the entire test period (phase 1 and phase 2), the T2 thesis appears to have a significantly higher average weight, ADG, with a lower FCR compared to the control group. The T2 thesis fixed a significantly (p < 0.01) greater quantity of nitrogen compared to the T1 thesis and control feed (T2 58.71% vs. T1 54.13% and control 54.02%). In conclusion, a low-protein diet without raw materials of animal origin proved more efficient in terms of performance and nitrogen retention.